Detection of Herpesvirus anguillae during two mortality investigations of wild European eel in England: implications for fishery management. (10th September 2013) - Armitage, J.; Hewlett, N. R.; Twigg, M.; Lewin, N. C.; Reading, A. J.; Williams, C. F.; Aprahamian, M.; Way, K.; Feist, S. W.; Peeler, E. J.
Abstract Herpesvirus anguillae (HVA) was detected during disease investigations of European eel, Anguilla anguilla L. at two stillwater fisheries in central England. These represent the first records of HVA from UK eels. Both mortalities were eel‐specific and took place during August 2009 and July 2010 at water temperatures between 17 and 19.4 °C. Pathological changes consistent with HVA infection included haemorrhaging in the fins, skin lesions and necrosis within the gills and liver. Transmission electron microscopy revealed active virion replication within the gill tissue. An initial assessment of risk is presented, indicating that HVA represents a high disease risk to UK eel stocks. However, further studies are required to establish the distribution of HVA before a reliable assessment of impact may be obtained. Until then, the detection of HVA holds important implications for eel conservation and management, in particular eel stocking activity.